LACTULOSE EFFICIENCY IN CONSTIPATION CORRECTION AMONG CHILDREN - L.N. Tsvetkova; L.V. Nechaeva; O.A. Goryacheva; T.F. Mukhina; E.G. Shcherba (Union of pediatricians of Russia, 2007)
The article analyzes lactulose efficiency (Normase, dr. reddy's laboratories, ltd., India) in correction of motor and evacuation and dysbiotic disorders among children, suffering from chronic constipations of the primary, secondary and functional genesis. The authors have observed 70 children (38 boys and 32 girls) aged between 1 and 15 years old for 10 months, who received a full course of observation and treatment in the gastroenterological department of Izmaylovskaya children's city clinical hospital with follow up examination in ambulatory conditions. The research findings they have acquired showed high lactulose efficiency in treatment of constipations among children, which justifies recommendations for the given medication in correction of the motor and evacuation large intestine function and disorders of its microflora.Key words: constipations, causes, treatment, lactulose, children.